2013
DOI: 10.5772/56320
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Filtering with IMM Algorithm for Ultra-Tight GPS/INS Integration

Abstract: This paper conducts a performance evaluation for the ultra‐tight integration of a Global positioning system (GPS) and an inertial navigation system (INS), using nonlinear filtering approaches with an interacting multiple model (IMM) algorithm. An ultra‐tight GPS/INS architecture involves the integration of in‐phase and quadrature components from the correlator of a GPS receiver with INS data. An unscented Kalman filter (UKF), which employs a set of sigma points by deterministic sampling, avoids the error cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…However, when measurement sub-systems return to work, the accuracy of the integrated navigation system returns promptly to the normal operation. In summary, the comparisons reported in this section are mainly with respect to [20,21] where a similar multi-sensor setup based on a SINS/GPS/BD2/CNS integrated navigation system is considered. The two scenarios considered in the paper are reported to achieve the following goals:

In Scenario 1, the goal is to evaluate the potential achievable performance improvements of the proposed methodology both in terms of the reduction in the false alarm rate and improvements in failure detection sensitivity.

…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, when measurement sub-systems return to work, the accuracy of the integrated navigation system returns promptly to the normal operation. In summary, the comparisons reported in this section are mainly with respect to [20,21] where a similar multi-sensor setup based on a SINS/GPS/BD2/CNS integrated navigation system is considered. The two scenarios considered in the paper are reported to achieve the following goals:

In Scenario 1, the goal is to evaluate the potential achievable performance improvements of the proposed methodology both in terms of the reduction in the false alarm rate and improvements in failure detection sensitivity.

…”
Section: Resultsmentioning
confidence: 99%
“…The two scenarios considered in the paper are reported to achieve the following goals:

In Scenario 1, the goal is to evaluate the potential achievable performance improvements of the proposed methodology both in terms of the reduction in the false alarm rate and improvements in failure detection sensitivity. In this regard, we present comparison results between the proposed algorithm and [20,21] to verify the validity of the proposed fault detection algorithm. It is observed that when we lower the accuracy of the inertial navigation unit, the algorithm proposed in [21] fails to work properly.

…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations